Platelet count and platelet indices in early life of infant with Retinopathy of prematurity - Wigit Kristianto; Martono Tri Utomo; Rozalina Loebis (Amaltea Medical Publishing House, 2024)
Background and objectives. Retinopathy of prematurity (ROP) is a complication of prematurity. Early detection of ROP is important because its management depends on prevention of severe ROP and its complications. Pro- and anti-angiogenic factors are involved in ROP pathogenesis. Platelet store and release these factors, but its role as predictor of ROP is still obscure. This study aimed to compare platelet count, mean platelet volume (MPV), platelet distribution width (PDW), and platelet mass index (PMI) value between two age groups in early life of infant diagnosed with ROP. Materials and methods. This study was retrospective study of medical record data of infants born at "Dr. Soetomo" General Academic Hospital Surabaya during 2021-2023. The infants were divided into two groups, they who have complete blood count result (CBC) in 0-7 days old (group 1) and 8-28 days old (group 2). We evaluated platelet count, MPV, PDW, and PMI value from CBC data. These data were analyzed using suitable statistical test. Results. Total of 126 infants were involved in this study. It consisted of 62 infants in group 1 and 64 infants on group 2. Platelet count was significantly different between groups (230.460±102.040/μL vs 313.664±182.890/μL, p=0,002). Value of MPV, PDW, and PMI were also significantly higher in group 2 (p<0.001). Frequency of thrombocytosis (>500.000/μL), high MPV (>10.05 fL), and high PMI (3640 fL/nL) were also significantly higher in group 2 (p<0.05). Conclusions. Higher platelet count, MPV, PDW, and PMI value were observed in 8-28 days old infant with ROP. They also more likely to experienced thrombocytosis, high MPV, and high PMI value.